Perancangan Model Simulasi Tata Letak Gudang Bahan Baku dengan Menggunakan Metode Shared Storage pada PT. Braja Mukti Cakra - Nadya Adira Fabiani; Parwadi Moengin; Sucipto Adisuwiryo (JURNAL TEKNIK INDUSTRI, 2019)
Braja Mukti Cakra (PT) is a company engaged in manufacturing that produces high-precision machined products, in the form of automotive components in Indonesia. Problems that occur at PT. Braja Mukti Cakra is in the warehouse of raw materials, where the laying of raw materials that are not optimal is due to the lack of naming and distribution of the types of raw materials on the shelves or pallets in the warehouse. This causes operators to have difficulty in finding raw materials to be sent to the production floor and causes the time to take raw materials to be long so that there will be delays in shipping to the production floor. The purpose of this study is to design a simulation model to improve the layout of the raw material warehouse from the storage area to the warehouse exit that can be used to evaluate the time taken for raw materials and the time of transfer of raw materials. In this study the first step is to evaluate the warehouse layout of raw materials using a checksheet to determine the condition of the current raw material warehouse and use a map of the raw material extraction process flow to determine the flow of the raw material extraction process. Next is the initial simulation model of raw material warehouse layout to understand the actual system. The model that has been built is then verified and validated. If the model is declared valid, improvements are made to existing problems by improving the warehouse layout of raw materials and the placement of existing raw materials using the shared storage method as a proposal for raw material warehouse layout. Standard raw placement, pay attention to raw materials that have the same purpose and are made into the same rack or pallet or located adjacent to the shelf or pallet to each other so as to get a shorter time in the shipping process. The number of proposed improvements in the raw material warehouse layout are 3 proposals. The first proposal is the addition of material handling, the second proposal uses the shared storage method and the third proposal uses shared storage methods and the addition of material handling. For the selection of the best proposals, the Benferonni method was used and used the results of the checksheet evaluation. The best proposal is the third proposal with the time of raw material collection and the transfer of raw materials to the warehouse exit which is equal to 71.18 hours. Compared with the initial simulation model which has the time to take raw materials and the transfer of raw materials to the warehouse exit of 122.23 hours. From this best proposal, it was obtained a time savings of 51.05 hours or 41.76%.